The Delta variant wave in Tunisia: Genetic diversity, spatio-temporal distribution and evidence of the spread of a divergent AY.122 sub-lineage - Haddad-Boubaker, Sondes; Arbi, Marwa; Souiai, Oussema; Chouikha, Anissa; Fares, Wasfi; Edington, Kate; Sims, Sam; Camma, Cesare; Lorusso, Alessio; Diagne, Moussa Moïse; Diallo, Amadou; Boubaker, Ilhem Boutiba Ben; et al. (Frontiers in Public Health, 2023)
Background. The Delta variant posed an increased risk to global public health and rapidly replaced the pre-existent variants worldwide. In this study, the genetic diversity and the spacio-temporal dynamics of Delta variant strains obtained in Tunisia, from May to December 2021 were investigated. Material and methods. 662 SARS-CoV2 genomes from human cases obtained during the Delta wave across Tunisia between May to December 2021 were used in this analysis. Viral whole genome and partial S-segment sequencing was performed using Illumina and Sanger platforms, respectively and lineage assignemnt was assessed using Pangolin version 1.2.4 and scorpio version 3.4.X Phylogenetic and phylogeographic analyses were achieved. Results: The age distribution of the infected cases showed a large peak between 25 to 50 years. Twelve Delta sub-lineages were detected nation-wide with AY.122 being the predominant variant representing 94.6% of sequences during the Delta wave. AY.122 sequences were highly related and shared the amino-acid change ORF1a:A498V, the synonymous mutations 2746T>C, 3037C>T, 8986C>T, 11332A>G in ORF1a and 23683C>T in the S gene. Spatiotemporal analysis indicates that the larger cities of Nabeul, Tunis and Kairouan constituted epicenters for the AY.122 sub-lineage and subsequent dispersion to the rest of the country. Conclusions: This study adds to the knowledge on the Delta variant and sub-variant distribution worldwide and documents genomic data from Tunisia, North Africa. It describes the transmission and dispersal patterns using epidemiological and sequencing data that may be helpful to understanding of future COVID-19 waves and variants.